Policy-based commitments in a post-2012 climate framework working paper - Lewis, Joanna; Diringer, Elliot; Pew Center on Global Climate Change (Arlington, Va. Pew Center on Global Climate Change, 2007)
This paper examines policy-based climate commitments as an element of a post-2012 international climate framework. It is part of a Pew Center series expanding on key recommendations of the Center's Climate dialogue at Pocantico.
I. Historical context : policies and measures -- II. Rationale for a policy-based approach -- III. Structuring policy commitments -- IV. Emissions crediting and other incentives -- V. Conclusions.
Includes bibliographical references (p. 26-28)
Keywords: Climatic changes -- International cooperation; Global warming -- International cooperation; Greenhouse gas mitigation -- International cooperation; Environmental law, International